Peran Inovasi Kemasan dalam Menjaga Stabilitas dan Keamanan Produk Farmasi: Sebuah Literature Review - Nabilah Nabilah; Ratna Habibah; Nor Latifah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Pharmaceutical packaging plays an important role in maintaining the stability, safety, and effectiveness of drug products during storage and distribution. Drug stability can be affected by various environmental factors such as temperature, humidity, oxygen, and light. Therefore, packaging innovation is a crucial strategy to extend the shelf life of drugs and maintain product quality, especially for sensitive preparations such as injections, transdermal patches, and biologics. This study is a literature review that aims to evaluate the impact of packaging innovation on the physical and chemical stability of pharmaceutical products. This study confirms that packaging selection is not just a technical aspect, but a vital strategy in ensuring pharmaceutical quality. Further research is needed to integrate smart packaging and advanced barrier technologies into modern pharmaceutical distribution systems.